Las agrupaciones de música popular en la conservación de las tradiciones culturales de la ciudad de Machala, provincia de El Oro. Periodo 2011 - 2012 - Lituma Quezada, Luis Felipe (2014)
To get proposed, the general objective consisted of rating function that meet groups of popular music in the preservation of the cultural traditions of the city, at the same time, it was necessary to use techniques and procedures that were used to determine the conservation of cultural traditions by the popular musical groups. To obtain the data, we use the same interview and survey techniques that were applied to the cultural authorities of the city of Machala, musicians of the popular musical groups and the citizenship of the downtown area of the city. The methodological foundations that allowed building the process and reaching accurate results went through the scientific method, as well as the techniques used in the process. The analytic–synthetic method, allowed the analysis and systematization of the results, the hermeneutic method allowed to interpret and test the hypothesis, collect, develop and interpret numerical data through the search of them and of their subsequent organization, analysis and interpretation. The master of this investigative study conclusion points out that the popular musical groups in the city of Machala are part of conservation and valorization of the same cultural traditions, since they are those who spread the art and music culture, influencing so positively in the formation of cultural and traditional of the inhabitants of the city, which is accompanied by the following recommendation to the authorities together with the popular musical groups of the City of Machala, which consists of continuously making free public concerts with interpretation of the canton traditional songs so that citizens know and value the preservation of music and Machaleñas cultural traditions.